A taxonomy for learning, teaching, and assessing : a revision of Bloom's taxonomy of educational objectives - Anderson, Lorin W.; Krathwohl, David R.; Airasian, Peter W.; Cruikshank, Kathleen, A.; Mayer, Richard E; Pintrich, Paul R.; Raths, James; Wittrock, Metlin C (New York : Longman, 2001)
This revision of Bloom's taxonomy is designed to help teachers understand and implement standards-based curriculums. Cognitive psychologists, curriculum specialists, teacher educators, and researchers have developed a two-dimensional framework, focusing on knowledge and cognitive processes. In combination, these two define what students are expected to learn in school. It explores curriculums from three unique perspectives-cognitive psychologists (learning emphasis), curriculum specialists and teacher educators (C & I emphasis), and measurement and assessment experts (assessment emphasis). This revisited framework allows you to connect learning in all areas of curriculum. Educators, or others interested in educational psychology or educational methods for grades K-12.
Includes bibliographical references (p. 323-331) and index.
Keywords: Education -- Aims and objectives; Taxonomy of educational objectives